2019
DOI: 10.3389/fdata.2019.00029
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Gender Analyses of Bibliographic Corpora

Abstract: The interplay between an academic's gender and their scholarly output is a riveting topic at the intersection of scientometrics, data science, gender studies, and sociology. Its effects can be studied to analyze the role of gender in research productivity, tenure and promotion standards, collaboration and networks, or scientific impact, among others. The typical methodology in this field of research is based on a number of assumptions that are customarily not discussed in detail in the relevant literature, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Despite these (and other) critiques, we have performed a namebased gender inference because academia is notoriously not gender agnostic and because gender disparities are indeed observed and need to be explained. We have discussed various concerns related to AGR in Mihaljević, Tullney, et al (2019) and would welcome ideas towards more inclusive schemas, preferably based on self-identification. Those would allow fairer, sustainable, and statistically significant analyses of bibliographic corpora in terms of gender.…”
Section: Gender Inferencementioning
confidence: 99%
“…Despite these (and other) critiques, we have performed a namebased gender inference because academia is notoriously not gender agnostic and because gender disparities are indeed observed and need to be explained. We have discussed various concerns related to AGR in Mihaljević, Tullney, et al (2019) and would welcome ideas towards more inclusive schemas, preferably based on self-identification. Those would allow fairer, sustainable, and statistically significant analyses of bibliographic corpora in terms of gender.…”
Section: Gender Inferencementioning
confidence: 99%
“…Second, like much of the literature on gender in science, the gender analysis by AlShebli et al engages in "Trans erasure" by failing to measure or thoughtfully acknowledge gender alternatives to cis men and cis women. These authors are not the first or only ones that fail to approach gender analyses in an inclusive way, which we and others have noted as a problem elsewhere 18,19 . We encourage scholars to both acknowledge the limitations of existing gender classification algorithms and strive to develop new measures, analyses, algorithms, and methods to include rather than erase trans and non-binary people.…”
Section: (4) Limitations Of Gender Classification Algorithmsmentioning
confidence: 83%
“…A larger list of ethical considerations associated with the NLP Scholar project is available through the project webpage. 21 Mihaljević et al (2019) also discusses the ethical considerations in using author names to infer gender statistics in the Gender Gap in Science Project. 22…”
Section: Q9 What Are the Limitations And Ethical Considerations Involved With This Work?mentioning
confidence: 99%
“…We discuss ethical considerations further in Section 6. See also Mihaljević et al (2019) for a discussion on ethical considerations in using author name to estimate gender statistics in the Gender Gap in Science Project-a large ongoing project tracking gender gaps in Mathematical and Natural Sciences. 4 Most studies on gender and authorship have found substantial gender disparities in favor of male researchers.…”
Section: Introductionmentioning
confidence: 99%